2008
DOI: 10.1111/j.1440-1738.2008.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Cretaceous paleogeography of Korea and Southwest Japan inferred from occurrence of detrital chromian spinels

Abstract: The Sindong Group was deposited in the north-south trending half-graben Nakdong Trough, southern Korean peninsula. The occurrence of detrital chromian spinels from the Jinju Formation of the Sindong Group in the Gyeongsang Basin means that the mafic to ultramafic rocks were exposed in its provenance. The chromian spinels from the Jinju Formation are characterized by extremely low TiO 2 and Fe 3+ . Moreover, their range of Cr# is from 0.45 to 0.80 and makes a single trend with Mg#. The chemistry of chromian spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Although detailed information was not provided, rounded zircon, tourmaline, rutile, and apatite are also present in Sindong Group sandstones in all areas, and are especially more common in the Nakdong and Hasandong formations, indicative of their derivation from sedimentary cover, consistent with the presence of sedimentary rock fragments. In addition, basic igneous rocks were also exposed locally from the beginning of the Sindong Group deposition, as evidenced by the occurrence of augite, a diagnostic mineral of basic igneous rocks, which is also supported by the occurrence of detrital chromian spinels (Hisada et al 2008; Y.I. Lee unpublished data).…”
Section: Provenance From Sandstone Petrographymentioning
confidence: 93%
“…Although detailed information was not provided, rounded zircon, tourmaline, rutile, and apatite are also present in Sindong Group sandstones in all areas, and are especially more common in the Nakdong and Hasandong formations, indicative of their derivation from sedimentary cover, consistent with the presence of sedimentary rock fragments. In addition, basic igneous rocks were also exposed locally from the beginning of the Sindong Group deposition, as evidenced by the occurrence of augite, a diagnostic mineral of basic igneous rocks, which is also supported by the occurrence of detrital chromian spinels (Hisada et al 2008; Y.I. Lee unpublished data).…”
Section: Provenance From Sandstone Petrographymentioning
confidence: 93%
“…Rifting affected a ~100‐ to 150‐km‐wide zone of the western margin of present‐day NE Honshu, leading to extensional basin formation and rapid subsidence (Martin, ; Nakajima, ; Yoshida et al, ). Hisada et al () and S. Kojima et al () suggested that prior to rifting, southwest Japan was located adjacent to the Korean peninsula based on geological correlation. Sillitoe () suggested that SE Korea and SW Japan shared a single metallogenic belt that appears to have been of offset by 200–250 km after its pre‐42 Ma formation and inferred that the belt was displaced along two major dextral strike‐slip faults, the Yangsan and Tsushima‐Goto faults (Figure ).…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, heavy minerals could be concentrated, but their chemical compositions have the potential to serve as indexes for provenance analysis. Many studies have revealed provenance based on the chemical compositions of heavy minerals, such as chromium spinel (Arai & Hisada, ; Hisada, Arai, & Lee, ; Hisada, Takashima, Arai, & Lee, ) and garnet (Takeuchi, ). However, the methods used in these studies are inconvenient for the following three reasons: (i) specific skills for mineral identification are needed; (ii) the methods are applicable to limited types of rocks, including target minerals; and (iii) extraction and concentration of target minerals are time‐consuming when large quantities of samples are employed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, heavy minerals could be concentrated, but their chemical compositions have the potential to serve as indexes for provenance analysis. Many studies have revealed provenance based on the chemical compositions of heavy minerals, such as chromium spinel (Arai & Hisada, 1991;Hisada, Arai, & Lee, 1999;Hisada, Takashima, Arai, & Lee, 2008) and garnet (Takeuchi, 1994). However, the methods used in these studies are inconvenient for the following three reasons: Recently, tremendous advances have been made in quantitative elemental analysis of micro domains by using techniques such as electron probe microanalysis (EPMA), secondary ion mass spectrometry, and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) (e.g.…”
mentioning
confidence: 99%